Reading Radio 4 - Daly, Macdonald. author. aut Link
XIII, 302 p.
Keywords: This book is a study of contemporary Radio 4 output, covering the entire broadcast day. Radio is largely neglected by media and cultural studies. The small body of existing work on Radio 4 is predominantly historical, focusing on institutional history, or sociological, focusing on contemporary BBC editorial and journalistic practices. Reading Radio 4, by contrast, analyses contemporary Radio 4 programmes entirely from the point of view of today’s listener. Individual chapters correspond to all existing Radio 4 timeslots in the entire broadcast day of 19 hours 40 minutes, from 5.20am to 1.00am. The study, while academic in approach, aims to promote an informed and critical appreciation of Radio 4 for all listeners, as well as students of the media. .